Algunas precisiones acerca de la filosofía moral experimental de David Hume - Calvente, Sofía Beatriz (2017)
Even though there is a general agreement among the scholars concerning the relationship between Hume and experimental philosophy, yet important Concerning the second one, we consider that there is a common ontological ground to moral and natural phenomena, because both fall into what Hume calls ‘matters of fact.’ This, in turn is what enables him to apply the same research method to both. In order to clarify the third item, we will delve into the central role that is given to facts, which Hume understands as epistemically relevant events, which are handled through explanatory reduction, Finally, we will show through some examples how Hume uses the method.